Religion and gender equality around the Baltic Sea
1 online resource.
Keywords: "This volume aims to rethink the intersections of gender and religion, as well as the secular and religious, in implementing and challenging gender equality at individual, institutional and societal levels in the regions around the Baltic Sea. Acknowledging the diversity of societies and the significance of socio-historical contexts, the empirical data discussed in the book draw attention to the under-researched region of post-socialist Baltic states. The analyses presented in the chapters are based on fieldwork carried out in Lithuania, Latvia, Estonia and Norway. The volume includes sociological, anthropological, historical, political science, and theological perspectives and covers five broad research areas: a shifting concept of gender equality and its developments in Baltic and Nordic countries; a diversity of developments within religious groups related to issues of gender equality and the negotiation of competing gender ideologies; inter-religious developments and gender equality; the role of religions in the construction of public discourse on gender equality; and religious socialization, focusing on the promotion of religious gender models through socialization and public education"--